2017
DOI: 10.1002/slct.201602011
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of Aqueous Citrate with Zn2+ and ZnO Nanoclusters: A Theoretical Study

Abstract: To gain insight into how citrate bonds to ZnO, we have studied how aqueous citrate bonds to zinc cations (Zn2+) as well as zinc oxide nanoclusters [(ZnO)n, n=8 to 12] through density functional theory modelling. The infrared (IR) spectra of each complex in water has been calculated at the M05‐2X/cc‐pVTZ level of theory with the SMD solvent model and is presented over the region of 1700 cm−1 to 1250 cm−1; this region corresponds to the stretching modes of the carboxylate group, which change when bonding occurs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Considering the suggested bonding structure of citrate to the ZnO surface, i.e. , one is “two terminal carboxylate groups” 41 and the other is “one terminal carboxylate group and one central carboxylate group as well as a hydroxyl group”, 42 both malic acid and tartaric acid, which have two carboxylate groups with one hydroxyl group, should have a growth-suppression effect on the ZnO crystals. However, the effect of both acids was significantly limited, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the suggested bonding structure of citrate to the ZnO surface, i.e. , one is “two terminal carboxylate groups” 41 and the other is “one terminal carboxylate group and one central carboxylate group as well as a hydroxyl group”, 42 both malic acid and tartaric acid, which have two carboxylate groups with one hydroxyl group, should have a growth-suppression effect on the ZnO crystals. However, the effect of both acids was significantly limited, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of both acids on the growth of the ZnO crystal explains the effect of the hydroxyl group in citric acid. Since malic acid has two carboxylate groups and one hydroxyl group, which are requirements for carboxylic acids coordinating on ZnO suggested by the above research, 41,42 it is expected to affect the growth of the ZnO crystal. Tartaric acid has two carboxylate groups and two hydroxyl groups and will show a similar effect to malic acid.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results are in agreement with previous studies, which, on the basis of IR, XPS, scanning tunneling microscopy (STM) and TEM analyses, indicated that the citrate anions form self‐assembled layers on Au NPs surfaces through central carboxylate groups thus stabilizing the (111) surface of the Au NPs . Moreover, density functional theory calculations also indicated that the citrate anion forms one or two monodentate bonds to different zinc ions within the ZnO nanoclusters and, in particular, attenuated total reflectance spectroscopy showed that the citrate anion strongly and selectively adsorbs to the (0001) ZnO face …”
Section: Discussionmentioning
confidence: 99%
“…[ 5,20,21,24,29,43–48 ] Usually, the adsorption proceeds in such a way that not all carboxyl groups coordinate to the surface. [ 29,43,44,46–50 ] On the one hand, this causes the stabilizing effect, but on the other hand, it also allows the free carboxyl groups to be used as basis for further modifications, which might otherwise not be possible on bare particle surfaces. Thus, citrate can be considered as a small but highly adhesive molecule that is capable to act as an anchor in order to modify different particles in the same way.…”
Section: Introductionmentioning
confidence: 99%